Characterisation of changes in the haemostasis system in dogs with thrombosis. (4th March 2013) - Bauer, N.; Moritz, A.
<x xml:space="preserve">Abstract</x> Objective To prospectively assess (2008 to 2009) all phases of coagulation including thromboelastography in dogs with thrombosis to determine if thrombosis is associated with hypercoagulable states. Methods Coagulation reaction in dogs with thrombosis (n = 7) diagnosed by diagnostic imaging or histopathology was compared with 56 control dogs. Dogs pretreated with antiplatelet and anticoagulation drugs were excluded. Thromboelastographic G‐values >10 · 3 Kdyn/cm2 were used to define a hypercoagulable state. Results Compared with the controls, there was a significantly higher mean platelet component indicating lower platelet activation status (17 · 99 ±1 · 36 versus 20 · 48 ±2 · 04 g/dL, P = 0 · 0004), increased thromboelastographic G‐value (6 · 4 ±1 · 6 versus 13 · 1 ±6 · 2 Kdyn/cm2, P = 0 · 0029), activated partial thromboplastin time, fibrinogen, D‐dimers (all: P < 0 · 0001) as well as decreased antithrombin (P = 0 · 0049), factor VIII (P < 0 · 0001), protein C (P < 0 · 0001), protein S (P = 0 · 0373) and activated protein C‐ratio (P = 0 · 0013). On the basis of thromboelastographic G‐value, three of six thromboelastographic tracings were classified as normocoagulable and three as hypercoagulable. Clinical Relevance In dogs with thrombosis, both normo‐ and hypercoagulable states are present and activated protein C resistance is common.